3+3x3-3+3=

a problem on order of operations:

3  +  3  x  3  -  3  +  3

3    +    9    -  3  +  3

12  -  3  +  3   =   9  +  3   =   12

answered Feb 10, 2013 by Level 4 User (5,600 points)
answered Aug 18, 2013 by Marco

Basic maths..

(3+3)x(3-3)+3= 3

3+3= 6

3-3= 0

6x0= 0

0+3= 3!
answered Mar 27, 2014 by anonymous
No parenthesis or exponents so multiply and divide left to right first

3+3x3-3+3 = 3+9-3+3

Then add and subtract left to right

3+9-3+9 = 12
answered Jun 17, 2014 by JSeym2000
3+3x3-3+3=
answered Jul 30, 2014 by anonymous
~~3+3x3-3+3=

6 x3=18-3=15+3=18
answered Sep 12, 2014 by lk
3+(3x3)-3+3 = 3+9-3+3 = 12-3+3 = 9+3 = 12 PEMDAS. when there is a multiplication symbol, the parenthesis are assumed automatically. even IF you left them out, you would multiply FIRST, then add/subtract left to right like normal.
answered Jun 19, 2015 by Deraya
12   3x3=9   9+3-3+3=12
answered Jun 19, 2015 by Bobbie
3+3*3-3+3=6

P there ae no parentheses

E there are no exponents

M 3+9-3+3

D there is no division

A do all of the addition (3+9)-(3+3) becomes 12-6

S do all subtraction 12-6= 6
answered Jun 20, 2015 by Chris
answered Feb 14, 2016 by Lin
P - N/A

E - N/A

M - (3x3) = 9

D - N/A

A - 3+(9)+3 = 15

S - 15-3 = 12

Any other solution is performing PEMDAS incorrectly.
answered Feb 14, 2016 by Bryan K. McDonald
(3+3)=6x3=18-(3+3)=6 so its 18-6=12
answered Mar 17, 2016 by kamaljit Singh

I have another question.

Why does everyone say that 3+3x3-3+3 equals to 12 or 18 when clearly, it's not the answer.

If you need to know what the answer is, you need to follow 'PEMDAS'.

----------------

PEMDAS:

1. P=Parentheses
2. E=Exponents
3. M=Multiplication
4. D=Division
6. S=Subtraction

----------------

1. 3+3x3-3+3 (Multiplication starts first) 3x3=9
3. 12-6 (Lastly, we subtract) 12-6=6 since 6x2=12

That's how to find the answer to the equation: 3+3x3-3+3=6

answered Jul 23, 2016 by anonymous
reshown Jul 24, 2016 by Rod

Parenthesis=none

Exponents=none

Multiplication= 3+(3x3)-3+3 = 3+(9)-3+3

Division =none